1998
DOI: 10.1063/1.367799
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling evidence of half-metallicity in epitaxial films of ferromagnetic perovskite manganites and ferrimagnetic magnetite

Abstract: Epitaxial diodes of a half-metallic ferromagnet on an oxide semiconductor J. Appl. Phys. 95, 7324 (2004); 10.1063/1.1669255 Enhancement of room temperature magnetoresistance in double perovskite ferrimagnets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 25 publications
(26 reference statements)
4
22
0
Order By: Relevance
“…The long-range order manifests itself by opening a gap in the electronic density of states (DOS) around the Fermi level (E F ). This gap was detected by photoemission [5,6], optical [7], and tunneling [8] spectroscopies. The effect of short-range ordering on the DOS is not as clear.…”
mentioning
confidence: 99%
“…The long-range order manifests itself by opening a gap in the electronic density of states (DOS) around the Fermi level (E F ). This gap was detected by photoemission [5,6], optical [7], and tunneling [8] spectroscopies. The effect of short-range ordering on the DOS is not as clear.…”
mentioning
confidence: 99%
“…Indeed, our previous optical studies of LCMO epitaxial films and single crystals [39][40][41] have revealed clear Drude-type optical conductivity below T C , implying bulk metallic behavior in the ferromagnetic state. Hence, the bulk characteristics of our LCMO samples determined from measurements of the magnetization, transport, and optical properties are all consistent with a metallic ferromagnetic phase, 21,22,35,[39][40][41] whereas manifestation of a gapped state is only found in surface sensitive measurements such as the STM and XPS studies, [17][18][19][20]35,36,42 suggesting that only the surface of LCMO is insulating. Similar results from optical measurements have also been reported for cleaved La 0.7 Sr 0.3 MnO 3 single crystals, 43 suggesting common metallic behavior in the bulk ferromagnetic phase of the manganites.…”
Section: Discussionmentioning
confidence: 85%
“…Although the occurrence of an energy gap in a nominally metallic manganite could not be explained by either band-structure calculations 10,11 or bulk electrical transport measurements, 21,22 the tunneling spectra of the metallic manganite over a wide energy range except near the Fermi level were actually consistent with theoretical calculations of the bulk electronic density of states. 17,18 Hence, it is reasonable to conjecture that the surface of manganites may be a thin layer with chemical compositions differing from those of the bulk. Thus, lower-bias ballistic electrons injected from the scanning tunneling microscopy ͑STM͒ tip could be more sensitive to the surface state, whereas ballistic electrons injected with higher bias could penetrate deeper into the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the half-metallicity reported experimentally from scanning tunnelling spectroscopy measurements. 38 The band gap in the minority spin states is 4.57 eV. The lower valence band DOS is mainly attributed to the O 2p and Mn 3d bands, which overlap for both compositions.…”
Section: Resultsmentioning
confidence: 92%